Governança orçamentária e a alocação de despesas públicas : uma análise no contexto do TRT17 - Pimentel, Yuri Garcia (2024)
The dissertation examines budget governance and the allocation of public expenses, with a case study at the Regional Labor Court of the 17th Region (TRT17), Espírito Santo. Initially, the text discusses the emerging concept of governance in the public sphere and how it responds to the crisis of the modern State, focusing on the transition from bureaucratic and hierarchical practices to models based on networks and the market, following New Public Governance perspectives. The general objective of the study is to analyze the implications of budgetary governance practices in decisions about expense allocation in TRT17. Specifically, it seeks to verify how elements of budget governance contribute to operational efficiency and influence decision-making, exploring variables such as transparency, integrity, participation and communication. Methodologically, the dissertation combines quantitative and qualitative approaches, including document analysis, TCU questionnaires and focus groups. The results indicate that effective budget governance practices are essential to ensure efficient allocations aligned with organizational goals, positively impacting public management